Laying claims on the city: young Mapuche ethnic identity and the use of urban space in Santiago, Chile. Issue 1 (2nd January 2020) - Merino, María-Eugenia; Webb, Andrew; Radcliffe, Sarah; Becerra, Sandra; Gloria Aillañir, Carmen
ABSTRACT: This article explores indigenous young people's use of different types of space within Santiago's unequally distributed opportunity structure to express cultural belonging and sense of place. Drawing on qualitative work informed by environmental psychology and critical geography, the article discusses how young Mapuche residents in Santiago elaborate practices and relations with their neighborhood, public areas and institutional space to establish ethnic identity. Although existing literature has demonstrated that non-essentialized indigenous identities and connections to land-territory are prevalent in urban spaces, attention has not been given to how these senses of belonging are situationally defined and negotiated across the city. We argue that place attachment and place identity are developed differentially and ambivalently within these contexts. That is, Mapuche indigenous youth and their households must navigate tensions between state-led action and personal agency, between politicized and quotidian identities, between "there" and "here, " and between past and present, so as to produce meaningful connections, activities, and affective relations according to distinct spatial dynamics and power relations.